Pengaruh Laju Alir Umpan Terhadap pH, Alkalinitas Dan Asam Volatil Dalam Bioreaktor Hibrid Anaerob Dua Tahap Pada Pengolahan Limbah Cair Industri Sagu - Resarizki Utami; Adrianto Ahmad; Edward HS (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
In producing sago becomes sago flour be required 20,000 liters of water per ton of sago, where 94% of the water be liquid waste. If the liquid waste which has a high content of organic material is directly dumped into waters, it is very potentially pollute theenvironment. One of the liquid waste processing sago is using by hybrid anaerobic bioreactor two stages. Bioreactor performance is influenced by pH, alkalinity and volatile acid. The purpose of this research is to know the influence of flow rate feedback of pH, alkalinity and volatile acid in hybrid anaerobic bioreactor two stages and determine the stability of the bioreactor. This research was conducted by using hybrid anaerobic bioreactor two stages with stone as a medium for growth of microorganisms. The volume of work being used is equal to 10 liters in the first stage biorector and 20 liters in thesecond stage bioreactor with variated flow rate feedback in the second stage bioreactor, 2.86 liters/day, 4 liters/day and 6.67 liters/day. The results showed that the optimum of flow rate feedback obtained at 2.86 liters/day with an average pH of 6.8, alkalinity of 2341 mg/L, volatile acid of 38,67 mg/L and the stability of bioreactor of 0.0118.Keywords : Alkalinity; Anaerobic; Hybrid bioreactor; pH; Sago watewater; Two stages; Volatile acid